Structural Organization and Function of the Golgi Ribbon During Cell Division - Ayala, Inmaculada; Colanzi, Antonino (Frontiers in Cell and Developmental Biology, 2022)
The Golgi complex has a central role in the secretory traffic. In vertebrate cells it is generally organized in polarized stacks of cisternae that are laterally connected by membranous tubules, forming a structure known as Golgi ribbon. The steady state ribbon arrangement results from a dynamic equilibrium between formation and cleavage of the membrane tubules connecting the stacks. This balance is of great physiological relevance as the unlinking of the ribbon during G2 is required for mitotic entry. A block of this process induces a potent G2 arrest of the cell cycle, indicating that a mitotic “Golgi checkpoint” controls the correct pre-mitotic segregation of the Golgi ribbon. Then, after mitosis onset, the Golgi stacks undergo an extensive disassembly, which is necessary for proper spindle formation. Notably, several Golgi-associated proteins acquire new roles in spindle formation and mitotic progression during mitosis. Here we summarize the current knowledge about the basic principle of the Golgi architecture and its functional relationship with cell division to highlight crucial aspects that need to be addressed to help us understand the physiological significance of the ribbon and the pathological implications of alterations of this organization.